Jual Beli Bedak Krim Berbahan Kimia Berbahaya Di Pasar Sangkumpal Bonang Kota Padangsidimpuan Ditinjau Dari Hukum Islam - Ikhwanuddin Harahap, Anita Novianti & Syafri Gunawan & (Jurnal El-Thawalib, 2020)
For most women, beauty is something very important. So that many cosmetics that are sold illegally do not have health insurance from the government, meaning that these cosmetics are very dangerous to health if consumed. From these problems, the compilers wanted to know how to buy and sell dangerous chemical based cream powders at the Sangkumpal Bonang Market, Padangsidimpuan City and how the Islamic Law Review regarding the Buying and Selling of Cream Powder at the Sangkumpal Bonang Market in Padangsidimpuan City